Institutional development and the dowry death curve across states in India. (28th May 2021) - Mitchell, Austin M.; Soni, Suparna
Abstract: Why do some informal institutions increase in prevalence while other informal institutions decline? We study why dowry deaths have increased with economic development in some Indian states but have decreased in others. We argue that when economic development is low, traditional institutions rather than state institutions govern behaviour. But as economic development increases to a high level, modern formal institutions replace traditional informal institutions. Women are increasingly exploited and murdered over dowry as incomes increase from a low level, but fewer deaths occur as incomes increase from a high level. We test this argument using a dataset of dowry deaths in years 2001–2011 for 32 Indian states and territories. Our paper contributes to understanding how exploitation through informal institutions rises and falls with economic development.